Hypercoagulability and the risk of myocardial infarction and ischemic stroke in young women. (21st August 2015) - Siegerink, B.; Maino, A.; Algra, A.; Rosendaal, F. R.
Summary Background Myocardial infarction (MI) and ischemic stroke (IS) are acute forms of arterial thrombosis and share some, but not all, risk factors, indicating different pathophysiological mechanisms. Objective This study aims to determine if hypercoagulability has a differential effect on the risk of MI and IS. Patients and methods We reviewed the results from the Risk of Arterial Thrombosis in Relation to Oral Contraceptives study, a population‐based case–control study involving young women (< 50 years) with MI, non‐cardioembolic IS and healthy controls. From these data, relative odds ratios (ORIS/ORMI) and their corresponding confidence intervals for all prothrombotic factors that were studied in both subgroups were calculated. Results Twenty‐nine prothrombotic risk factors were identified as measures of hypercoagulability. Twenty‐two of these risk factors (21/29, 72%) had a relative odds ratios > 1; for 12 (41%), it was > 2; and for 5 (17%), it was > 2.75. The five risk factors with the largest differences in associations were high levels of activated factor XI (FXI) and FXII, kallikrein, the presence of lupus anticoagulans, and a genetic variation in the FXIII gene. Conclusion In young women, prothrombotic factors are associated more with the risk of IS than with MI risk, suggesting a different role of hypercoagulability in the mechanism leading to these two diseases.